2019
DOI: 10.1155/2019/6987427
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Evolutionary Game System and Control Strategies of Behavior Instability in Coal Mine Safety Management

Abstract: In this paper, we try to find the right control method for the game behavior instability in coal mine safety management. Through the analysis and comparison of the system stability with inflexible and flexible costs and penalties, it can be concluded that the dynamical game system with flexible costs (incentive rewards) and flexible penalty mechanism can significantly reduce the dynamics of unsafe behaviors in coal mine safety supervision. A combined mechanism of incentive rewards and flexible penalty is put f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…However, the involved game participants are different; some games occur between coal mines, and some occur between coal mines and miners. ere are relatively few papers on tripartite games [30][31][32]. e content of existing work has some drawbacks, and there has been a lack of rigorous mathematical demonstration [33,34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the involved game participants are different; some games occur between coal mines, and some occur between coal mines and miners. ere are relatively few papers on tripartite games [30][31][32]. e content of existing work has some drawbacks, and there has been a lack of rigorous mathematical demonstration [33,34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of the game problem between the stakeholders in the production system of a coal mine, Lu and Wang conducted relevant research on the fractional supervision game model [24], the multiple evolution game model [25], the stability of the evolution game system [26], and the evolution dynamics model based on the delay and impulsive differential equation [27]. Furthermore, some authors have analyzed the dynamic process of a multiplayer game in a coal mine safety supervision system [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…As a controlling method of unsafe behaviors, CMSM has already attracted many scholars' attention [6][7][8][9][10]. Based on the theoretical analysis of the evolutionary stability strategy, we have already put forward some incentive measures and restraint measures to control the instability of player's dynamical behaviors in CMSM [11]. It is found that game strategy selection is controllable under the corresponding measures, and appropriate incentive and constraint measures can mobilize the initiative of safe behaviors.…”
Section: Introductionmentioning
confidence: 99%